Ingroup and outgroup preference and rejection among young children of different ethnic groups in the Netherlands. Issue 1 (19th September 2022) - Pektas, Fadime; Emmen, Rosanneke A. G.; Mesman, Judi
Abstract: The current study investigated the ethnic hierarchy in ingroup and outgroup preference and rejection among 6‐ to 10‐year‐old children of the dominant White Dutch group ( n = 145), and the underrepresented Turkish‐Dutch ( n = 78), and Afro‐Dutch ( n = 57) groups (55% girls, M = 7.49, SD = .98) in the Netherlands. Results from a social preference task indicated that White Dutch children showed clearly more preference for their own ethnic group (ingroup preference) compared to the two outgroup preferences (Middle Eastern and Black), while Turkish‐ and Afro‐Dutch children showed limited ingroup preference. Both White and Turkish‐Dutch children showed less preference for and more rejection of the Black outgroup compared to Afro‐Dutch children. Younger children showed more Black rejection compared to older children. This study provides much‐needed evidence for the generalizability of prejudice patterns in children beyond the United States, and suggests that interventions aimed at improving interethnic relations are already relevant at primary school age.